The Differences in Indoleamine 2,3-dioxygenase 1 Plasma Activity of HIV-Positive Pulmonary Tuberculosis and HIV-Negative Pulmonary Tuberculosis - Roza Kurniati; Dwitya Elvira; Rido Wandrivel (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Tuberculosis is the most common cause of death in HIV patients. Indoleamine 2,3-dioxygenase 1 (IDO1) is an enzyme that plays a crucial role in the immune response to TB and HIV infection. Increased plasma IDO1 activity in TB patients can be a promising marker for the diagnosis of TB, especially in HIV patients. This study aimed to evaluate the differences in the activity of indoleamine 2,3-dioxygenase 1 plasma of HIV-positive pulmonary TB with HIV-negative pulmonary TB patients. Methods: This study is an analytic observational study. Plasma IDO1 activity was assessed by calculating the kynurenine/tryptophan ratio (K/T ratio). This indicator was assessed on 28 lung TB patients divided into two groups, HIV-positive pulmonary TB and HIV-negative pulmonary TB group. Results: Twenty-eight subjects were included in this study with a mean age of 42,96 (16,17) years, with more males than females. This study's mean K/T ratio was 0.18 (0.16), with HIV-positive pulmonary TB is higher than HIV-negative pulmonary TB (0.24 vs 0.12, p = 0.027). Conclusion: There is a significant difference in the Indoleamine 2,3-dioxygenase 1 (IDO1) plasma in HIV-positive pulmonary TB and HIV-negative pulmonary TB groups. Thus the IDO1 plasma can be used as a new biomarker in diagnosed TB in HIV patients.